(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article explores the socio-economic significance of developing bioeconomy and circular economy in Uzbekistan. It discusses the main directions of bioeconomy and the principles of circular economy, analyzing their role in stabilizing the national economy. The research findings indicate that fostering bioeconomy and circular economy can enhance economic efficiency, protect the environment, and ensure rational resource utilization. These approaches are crucial for achieving sustainable development and maintaining environmental safety.